2017
DOI: 10.1016/j.neuroimage.2016.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance fingerprinting based on realistic vasculature in mice

Abstract: Magnetic resonance fingerprinting (MRF) was recently proposed as a novel strategy for MR data acquisition and analysis. A variant of MRF called vascular MRF (vMRF) followed, that extracted maps of three parameters of physiological importance: cerebral oxygen saturation (SatO2), mean vessel radius and cerebral blood volume (CBV). However, this estimation was based on idealized 2-dimensional simulations of vascular networks using random cylinders and the empirical Bloch equations convolved with a diffusion kerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The T1 and T2 values obtained with MRF studies have shown good correlation with conventional T1 and T2 mapping methods and those published in literature[14,16,4446]. The utility of MRF has also been demonstrated in preclinical and animal studies[12,21]. Clinical applications of MRF till date have been greatly focused on brain and prostate and shown promise in abdomen, musculoskeletal and cardiac applications.…”
Section: Current Mrf Applicationsmentioning
confidence: 63%
See 2 more Smart Citations
“…The T1 and T2 values obtained with MRF studies have shown good correlation with conventional T1 and T2 mapping methods and those published in literature[14,16,4446]. The utility of MRF has also been demonstrated in preclinical and animal studies[12,21]. Clinical applications of MRF till date have been greatly focused on brain and prostate and shown promise in abdomen, musculoskeletal and cardiac applications.…”
Section: Current Mrf Applicationsmentioning
confidence: 63%
“…Each of these steps is discussed in more detail below. While the original MRF description focused on measuring T1, T2, static magnetic field (B 0 ) inhomogeneity or off-resonance frequency and proton density M 0 [2], recent work has shown the feasibility to measure other properties such as radio frequency (RF) transmit field inhomogeneity (B 1 )[6,7], T2*[8], perfusion[9] and microvascular properties[1012]. …”
Section: Mrf Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the transient‐state signal can provide quantitative information about T 1 , T 2 , B 0 , B 1 + , and other parameters depending on the applied MRF pattern (i.e., the excitation, gradients, and timing pattern). Besides these parameters, attempts to quantify physiological parameters such as diffusion or tissue vascularization have been pursued …”
Section: Introductionmentioning
confidence: 99%
“…Besides these parameters, attempts to quantify physiological parameters such as diffusion or tissue vascularization have been pursued. 5,6 Another physiological parameter of rising interest and with strong potential for MRF is the blood flow velocity. 7 Time-resolved quantification of flow velocities is used in clinical routine for investigating cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%